Associative electrolyte solution near the charge hard wall. Density, charge, polarization and potential profiles - Kapko, V.I.; Holovko, M.F. (Condensed Matter Physics, 2001)
The density, charge, polarization and potential profiles of a simple model
of an associative electrolyte are studied in an associative mean spherical
approximation (AMSA). The limits of the full association and complete disassociation
are considered. Профілі густини, заряду, поляризації і потенціалу простої моделі асоціативного електроліту вивчаються в асоціативному середньо-сферичному наближенні (АССН). Розглядаються границі повної асоціації
і дисоціації.